Masonry Wall Performance Estimation Under Blast Loading: A Study Using Finite Element Analysis - Muhammad Arif Husni Mubarok; Halim Hamadi; Quang Thang Do; Siti Nurlita; Afiq Azfar Pratama; Rommy Rommy (Mekanika)
This paper studies the dynamic response of masonry wall structures under blast loading. It requires a detailed understanding of the explosion phenomenon, wave propagation, and the structure's response to these shocks. The blast load is applied to the surface of the masonry wall. The main focus is to evaluate the dynamic response of a masonry wall due to a blast load. We used the Finite Element Method (FEM) for modeling the dynamic structural response to explosions. The explicit finite element modeling and analysis are done using ABAQUS CAE software. In this study, the model uses materials, namely Masonry. Masonry could be a composite structure entrenched by blocks of bricks articulated by mortar joints. In this study, the properties of the material used are clay bricks masonry as orthotropic materials. The structural analysis carried out in this study is related to stress, strain, and deformation due to the given loading.